Determination of selected neurotoxic insecticides in small amounts of animal tissue utilizing a newly constructed mini-extractor - Seifertová, Marta; Čechová, Eliška; Llansola, Marta; Felipo, Vicente; Vykoukalová, Martina; Kočan, Anton (Analytical and bioanalytical chemistry, 2017)
We developed a simple analytical method for the simultaneous determination of representatives of various groups of neurotoxic insecticides (carbaryl, chlorpyrifos, cypermethrin, and α-endosulfan and β-endosulfan and their metabolite endosulfan sulfate) in limited amounts of animal tissues containing different amounts of lipids. Selected tissues (rodent fat, liver, and brain) were extracted in a special in-house-designed mini-extractor constructed on the basis of the Soxhlet and Twisselmann extractors. A dried tissue sample placed in a small cartridge was extracted, while the nascent extract was simultaneously filtered through a layer of sodium sulfate. The extraction was followed by combined clean-up, including gel permeation chromatography (in case of high lipid content), ultrasonication, and solid-phase extraction chromatography using C18 on silica and aluminum oxide. Gas chromatography coupled with high-resolution mass spectrometry was used for analyte separation, detection, and quantification. Average recoveries for individual insecticides ranged from 82 to 111%. Expanded measurement uncertainties were generally lower than 35%. The developed method was successfully applied to rat tissue samples obtained from an animal model dealing with insecticide exposure during brain development. This method may also be applied to the analytical treatment of small amounts of various types of animal and human tissue samples. A significant advantage achieved using this method is high sample throughput due to the simultaneous treatment of many samples. Graphical abstract Optimized workflow for the determination of selected insecticides in small amounts of animal tissue including newly developed mini-extractor.
Keywords: játra; Limit of Detection; tuková tkáň; gelová chromatografie; limita detekce; neurotoxiny; insekticidy; extrakce na pevné fázi; Equipment Design; Female; krysa rodu Rattus; zvířata; Neurotoxins; Insecticides; Brain Chemistry; mozek - chemie; plynová chromatografie s hmotnostně spektrometrickou detekcí; ženské pohlaví; Liver; Adipose Tissue; design vybavení; Solid Phase Extraction; Rats; Animals; vibrace ultrazvukové; Sonication; Gas Chromatography-Mass Spectrometry; Chromatography, Gel